Women of color in higher education changing directions and new perspectives - Lloyd-Jones, Brenda; Jean-Marie, Gaëtane; Frierson, Henry T. (Henry Taylor), 1944-; Tate, William (Diversity in higher education, 2011)
Ask practically any academic department chair why they do not have more African Americans among faculty members and they generally respond with stock stories or folktales, which stimulated the title of this volume. Stock stories are akin to grand narratives that explain 'why things are' in ways that satisfy those in dominant positions. Frierson and Tate argue it is time to move beyond these. The purpose of the book is to provide historical, conceptual, and empirically-based analyses focused on the development of African Americans in STEM fields. There is rarely any real understanding of the uneven contours of the education pipeline or the transition to academic life experienced in these situations and this volume will shed light on opportunities to advance African American attainment in STEM disciplines throughout the academic and professional spectra, and the mitigation of disparities that continue to be so prevalent. The editors hope that it will generate discussions and actions that are based on empirical evidence and policy analyses, rather than long standing stock stories and folktales that misrepresent the paths linked to African Americans attainment in STEM fields.